2004
DOI: 10.1002/jsfa.1621
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical characterisation of unextractable seed coat pigments and quantification of extractable lignin in the Brassicaceae

Abstract: The differences determined by in situ histochemical staining and thioglycolic lignin analyses provided a new view of seed coat composition in a range of yellow-and brown-seeded germplasm of the Brassicaceae. Unextractable seed coat pigments were composed of proanthocyanidin (condensed tannin) polymers. Anthocyanins were absent in all seed coat tissues. Proanthocyanidin was deposited over the entire seed coat in dark-seeded germplasm and in patches in some yellow-seeded germplasm. The seed coat and hilum of Cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 46 publications
7
88
2
3
Order By: Relevance
“…Extensive chemical analysis of other black seeded B. napus lines (Durkee 1971;Leung et al 1979;Mitaru et al 1982;Naczk et al 1998) and elucidation of flavonoid biochemistry in general (Marles et al 2003a;Marles and Gruber 2004) have provided a sound basis to apply metabolite profiling to probe the genetic causes of yellow seed trait. For example, Marles et al (2003b) compared a yellowseeded and a brown-seeded type found in a seed lot of Brassica carinata (BB CC genome) after selfing the lines and showed that the yellow seed had lower levels of DFR expression.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive chemical analysis of other black seeded B. napus lines (Durkee 1971;Leung et al 1979;Mitaru et al 1982;Naczk et al 1998) and elucidation of flavonoid biochemistry in general (Marles et al 2003a;Marles and Gruber 2004) have provided a sound basis to apply metabolite profiling to probe the genetic causes of yellow seed trait. For example, Marles et al (2003b) compared a yellowseeded and a brown-seeded type found in a seed lot of Brassica carinata (BB CC genome) after selfing the lines and showed that the yellow seed had lower levels of DFR expression.…”
Section: Discussionmentioning
confidence: 99%
“…During seed maturation, PAs form oxidized complexes with cell wall polysaccharides, other phenolics and/or proteins, thus imparting a dark colour to the seed tissues (reviewed in Moïse et al 2005). A similar structure and development of the seed coat have been described for other Brassica species (Ren and Bewley 1998;Marles 2001;Zeng et al 2004) and Arabidopsis thaliana (Devic et al 1999;Beeckman et al 2000;Debeaujon et al 2003;Haughn and Chaudhury 2005), except that the number of cell layers per integument and the contribution of the seed coat to the total seed mass differ from one species to the other .…”
Section: Introductionmentioning
confidence: 88%
“…Also, a recent study demonstrated that thioglycolic lignin was signiWcantly lower in yellow seededsamples compared with the dark-seeded accessions in Brassicaceae (Marles and Gruber 2004). Thus we also examined the extractable lignin content in the mature mutant and wild-type seeds (Campbell and Ellis 1992;Marles and Gruber 2004).…”
Section: Mutations In Atlac15 Altered the Seed Coat Colormentioning
confidence: 98%